O uso do peixe-zebra em modelos de obesidade e diabetes: alterações comportamentais e bioquímicas - Zortéa, Nágila Bernarda (2020)
Obesity is a chronic non-communicable disease, which has been considered a worldwide epidemic that increases the risk for other chronic diseases, including cardiovascular disease and diabetes mellitus II (DMII). DMII is of metabolic etiology, characterized by decreased pancreatic insulin secretion and / or tissue resistance to insulin, deficient in hyperglycemia and glycotoxicity. Obesity and DMII cause morbid changes such as cardiovascular disease, hypertension, multiple organ failure, amputations and blindness. Both pathologies are complex and involve genetic and environmental factors, which cause consequences in various tissues such as fat, musculoskeletal and organs such as the liver and pancreas. The zebrafish model is a promising model in metabolic research, to present advantages such as rapid development, optical transparency of the fertilized embryo, treatable genetics, ease of maintenance, in addition to maintaining its functional conservation of lipid metabolism, glucose homeostasis, structure of the pancreas and present digestive organs as well as adipose tissue, central and autonomic nervous system, install a high degree of genetic, anatomical and physiological similarity with human beings. The objective of this dissertation is to verify the morphometric, biochemical and behavioral changes in this animal model, through an experimental study of diabetes obesity induction with overfeeding and glucose treatments. This study was approved by the Research Ethics Committee and followed all the rules of the National Council for the Control of Animal Experimentation (CONCEA). The study induced fish to 4 treatments: Control, Glucose, Overfeed and Overfeed plus Glucose. Results: Our alternative results to changes in morphometric, behavioral and biochemical patterns with fish treated with overfeeding. Fish treated with glucose treated, behavioral and morphometric changes. Conclusion: Overfeeding and glucose exposure affect the behavior and alter the lipid profile of zebrafish. We conclude that this animal model and these treatments are important for promoting research on diseases of obesity and diabetes.